2016
DOI: 10.15353/cjds.v5i2.275
|View full text |Cite
|
Sign up to set email alerts
|

Access Barriers to Health Care among People with Disabilities in the Kumasi Metropolis of Ghana

Abstract: Health care is a human right yet access barriers to health care remain one of the major challenges among people with disabilities. One of the several reasons accounting for this is that there is little evidence on access barriers to healthcare among people with disabilities. This partly explains the gaps in policy design and implementation of appropriate interventions for people with disabilities. This study aimed at contributing to filling the evidence gaps on access barriers to healthcare among people with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 13 publications
6
66
1
Order By: Relevance
“…Earlier studies also conclude that people with disabilities faced numerous physical structural and environmental barriers in seeking care, including for SRH services. 7,8,11,12,14,39,40 This study underscores the need to reassess and improve the physical structure of health facilities, taking into consideration different disabilities.…”
Section: Affordabilitymentioning
confidence: 80%
See 2 more Smart Citations
“…Earlier studies also conclude that people with disabilities faced numerous physical structural and environmental barriers in seeking care, including for SRH services. 7,8,11,12,14,39,40 This study underscores the need to reassess and improve the physical structure of health facilities, taking into consideration different disabilities.…”
Section: Affordabilitymentioning
confidence: 80%
“…Published papers from LMICs have concluded that women with disabilities have limited understanding of SRH services and care and are thus less likely to access services and care due to a lack of inclusive and accessible information and communication. 8,11,13,14 Women with disabilities face numerous access barriers in accessing SRH services and care compared with the general population. [7][8][9][10][11][12][13] These barriers are interrelated and similar across different settings 15 and can be categorised broadly into those related to physical structure, transportation, finance, communication and stigmatising attitudes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors such as prohibitive cost and limited availability of health care services, physical barriers to visiting health care facilities, inadequate knowledge and skills on the part of health care providers and perceived discrimination have a negative impact on PWPDs and prevent them from seeking health care [68]. Socio-demographic characteristics such as age, socio-economic status, education and place of residence also have a strong influence on health care seeking behaviour of PWPDs [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several empirical studies have been undertaken on access to health services for people with disabilities. These studies have largely focused on the barriers to accessing health services for people with physical disabilities [17][18][19]. However, little empirical evidence is known about SRH services and care information.…”
Section: Introductionmentioning
confidence: 99%